Development of Coconut Dehusker Machine for Small Scale Industry - Fithra Herdian; Sri Aulia Novita; Indra Laksmana; Mohammad Riza Nurtam; Rildiwan Rildiwan; Zulnadi Zulnadi (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2019)
West Sumatra-Indonesia has potential to plant coconut due to the coastal location, sunshine level with average temperature 27oC. Coconut is a very productive plant. Coconut dehusking is one of the process that takes a lot of time and energy. Most of the farmer still using human manual labour with the help of tools made of iron or wooden crowbar that is mounted standing vertically with the blade facing upward about 80 cm from the ground. To increase the number of coconut products, it is designed the coconut dehusker machine. The main component of the machine were two rollers that rotate each other in opposite directions with each roller embedded iron-shaped nails that work to tear the coconut husk. Each roller has a different rotational speed. This machine has dimensions of 98 cm x 51 cm x 95 cm. Roller length is 50 cm and diameter 4 inches. The power source of the machine is a 2 HP electric motor, the speed was reduced by using 2 speeds reducer with the ratio of 1:20 and 1:30 respectively. From the performance test of this machine can dehusk 100 coconuts per hour. The operational basic cost of the machine equal to Rp 129.89 per coconut (about 1 cent) and Break Event Point is 12.387 coconut per year from the result of the performance test. From the economic analysis machine can be concluded that the use of this machine is better when compared to human labour which has limitation to duration and capacity.